2014
DOI: 10.1103/physrevc.89.035205
|View full text |Cite
|
Sign up to set email alerts
|

Baryon stopping in the color glass condensate formalism: A phenomenological study

Abstract: The net-baryon production at forward rapidities is investigated considering the Color Glass Condensate formalism. We assume that at large energies the coherence of the projectile quarks is lost and that the leading baryon production mechanism changes from recombination to independent fragmentation. The phenomenological implications for net-baryon production in pp/pA/AA collisions are analysed and predictions for LHC energies are presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 83 publications
0
16
1
Order By: Relevance
“…In fact, there is no symmetry due to the density distributions of scatter points in the two directions being totally different. Two small high density areas appear in the regions of large | | Although Lambda decays affect the rapidity distribution somewhere, we have analyzed the net-baryons but not the net-protons measured by the BRAHMS Collaboration [17][18][19] due to more abundant data of net-baryons being collected in [20]. It is more convenient for us to use [20] instead of [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, there is no symmetry due to the density distributions of scatter points in the two directions being totally different. Two small high density areas appear in the regions of large | | Although Lambda decays affect the rapidity distribution somewhere, we have analyzed the net-baryons but not the net-protons measured by the BRAHMS Collaboration [17][18][19] due to more abundant data of net-baryons being collected in [20]. It is more convenient for us to use [20] instead of [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Two small high density areas appear in the regions of large | | Although Lambda decays affect the rapidity distribution somewhere, we have analyzed the net-baryons but not the net-protons measured by the BRAHMS Collaboration [17][18][19] due to more abundant data of net-baryons being collected in [20]. It is more convenient for us to use [20] instead of [17][18][19]. In addition, the typical motivation to study net-baryons is that one expects it to be transported in the initial collisions and there one uses that it is conserved to locate it in the final state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DHJ formula was also utilized to compute baryon productions for Au+Au collisions in Ref. [23,24], and it is found that transverse momentum spectra and net-baryon rapidity distributions in Au+Au collisions at RHIC are well described with the DHJ formula.…”
Section: Introductionmentioning
confidence: 99%